Evaluation of a Low-threshold Exercise And Protein supplementation intervention for Women (LEAP-W) experiencing homelessness and addiction: Protocol for a single-arm mixed methods feasibility study - Fiona Kennedy; Deirdre Murray; Clíona Ní Cheallaigh; Roman Romero-Ortuno; Julie Broderick (PLoS ONE, 2025)
Background Frailty is a complex multi-dimensional state of increased vulnerability to adverse outcomes and is associated with older age but there is growing evidence of accelerated ageing and frailty in non-geriatric populations, including those experiencing socio-economic deprivation and extreme social exclusion, such as people experiencing homelessness. Addiction, as a coping mechanism for prior trauma, is common among people who are homeless and can have a gendered dimension. Women experiencing homelessness and addiction have unique needs which require a gendered approach. The aim of this study is to evaluate the feasibility and impact of an exercise intervention to target the known physical functioning deficits and frailty which this population experiences. Methods This quantitatively driven, sequential single-arm mixed-methods feasibility study will evaluate the feasibility and impact of a low threshold trauma informed exercise intervention on physical functioning and frailty in women experiencing homelessness and addiction. Physical function (10m Walk Test, 2Min Walk Test, Single Leg Stance, Chair Stand Test, hand grip dynamometry), frailty (Clinical Frailty Scale and the SHARE-Frailty Instrument) and nutritional status (Mini-Nutritional Status), pain (Numerical Rating Scale) and quality of life (SF 12-V2) will be evaluated. The 10-week intervention will involve a 3-times weekly exercise programme with protein supplementation. Following this, qualitative interviews, which will be thematically analysed using Braun & Clarke methodology, will be conducted. This study will be conducted in Dublin from February to July 2024. Discussion Little is known about frailty-focussed interventions in women experiencing homelessness and addiction. This proposed study will help to increase the knowledge base regarding the physical health burden and frailty experienced by this vulnerable population and will deliver a targeted intervention with a gendered dimension to mitigate its affects. The findings of this research will help narrow the research gap and will guide clinicians and policy makers to implement unique gender-based treatment strategies for this population. (300). Clinical trials.gov number NCT05700305.